Inter-primer binding site (iPBS) retrotransposon markers provide insights into the genetic diversity and population structure of carrots (Daucus, Apiaceae) - Yildiz, Mehtap (2022)
Studies of genetic diversity and population structure are essential as an initial step in conservation and breeding programs for modern crops. Carrot (Daucus spp.) is among the ten most important vegetables worldwide, however, its genetic structure and phylogenetic relationships are not totally deciphered. Here, we explored the utility of 21 inter-primer binding site (iPBS) retrotransposon markers to determine the genetic diversity and population structure of 38 accessions of Daucus and one accession of a related genus. The manual scoring revealed 309 bands based on their presence/absence. The dendrogram based on the UPGMA clustering algorithm and a principal coordinate analysis (PCoA) indicated the presence of four clusters. The Daucus species with 2n = 18 chromosome (subclade A´) separated from the other two species D. pusillus and D. muricatus, which were positioned into two individual clusters. The other clade includes the Daucus from the B group. It was also noticed that few accessions were intermixed amongst clusters. Different genetic diversity parameters were estimated based on the four clusters (populations) defined by STRUCTURE software, demonstrating that clusters 3 and 4 possessed the lowest and highest diversity values, respectively. AMOVA showed variation between and within clusters of 41.85% and 58.15%, respectively. The highest population divergence (Fst) was observed between clusters 2 and 3 (0.579), on the other hand, clusters 1 and 4 depicted the lowest Fst with 0.160. Our research highlighted that iPBS markers were successful and effective to study Daucus genetic diversity. These results will contribute to the genetic improvement of carrots and sustainable management of its diversity.